ARCHAEOLOGISTS’ APPROACH TO GENDER AND BIOLOGICAL SEX WITH CONCENTRATION ON IRON AGE ERA IN KAZAKHSTAN - Saktaganova, Galiya (Nazarbayev University School of Sciences and Humanities, 2024)
This research explores whether archaeologists in a specific Kazakhstani concept have utilized and applied the concepts around gender and biological sex, and whether current perceptions of gender have influenced their conceptions. The researcher has conducted interviews with anthropologists working in Kazakhstan, as well as has done some participant observations on lectures centered around gender and anthropological methodologies. This research has examined the current state of the debate revolving around concepts of gender and sex in Iron Age archaeology, and explored one of the many conversations centered around the ways gender and sex is being discussed in Kazakhstani archaeology.
Keywords: type of access: gated access; archaeology; gender; sex; feminist archaeology; Iron Age Kazakhstan